Student organizational citizenship behavior: Nature and structure among students in elementary and middle schools. (July 2019) - Blondheim, Gefen, F.; Somech, Anit
Abstract: This research studied the nature of organizational citizenship behavior (OCB) among elementary and middle school students. While much is known about OCB in a large variety of contexts (Jimmieson, Hannam, & Yeo, 2010), this research is the first ever to study the unique construct of student OCB. In-depth semi-structured interviews were conducted with principals, teachers, and students. The interviews were analyzed using thematic network analysis, revealing five dimensions of student OCB: OCB toward studenthood, helping behavior toward students, OCB toward school personnel, OCB toward school community, and OCB toward external society. Practical implications and significance for future research are discussed. Highlights: All interviewees pointed toward studenthood as the main aspect of students' in-role expectations. All interviewees were able to identify students' citizenship behaviors. OCB's dimensions: Toward studenthood, school personnel, school community, external society, and helping behavior.